El Terrorismo y la gobernabilidad en el Perú - trelles vizquerra, javier (2022)
This article analyzes the terrorism actions carried out by Sendero Luminoso (SL), from the capture of its leader Abimael Guzmán comrade “Gonzalo” to date and its influence on the governability of Peru. As is well known, the OT-SL has changed its strategy of action as a result of the capture of its leader, that is, from the armed and violent struggle that caused much material destruction and numerous deaths, to a different action, by peaceful means. and in an underground way, being the most important, the creation of its political arm called the Movement for Amnesty and Fundamental Rights (MOVADEF) and later numerous Front Organizations, which are allowing it to continue its long-term strategy, in search of the capture of power, consistent with its "Marxist-Leninist-Maoist" ideology, first undermine the established democratic system, and then establish a state consistent with its political ends, through political indoctrination in universities, organizations related to its ideology, infiltrating in public institutions of the State, actively participating in strikes, mobilizations, and in various social conflicts (miners, coca growers, etc.) many times inciting the generation of public disorder and generating acts of violence to discredit the government, affecting this action to the governability of the country. Key Words: Terrorism, MOVADEF, front organizations, violence, governability.